Association between the use of protease inhibitors in Highly Active Antiretroviral Therapy (HAART) and incidence of metabolic syndrome in HIV-infected patients: A systematic review and meta-analysis - Echecopar-Sabogal, Jose (2017)
Introduction: Since its introduction, Highly Active Antiretroviral Treatment (HAART) has been shown to prolong the life expectancy of HIV-infected patients. HIV and HAART, especially protease inhibitors (PIs), have been associated with the occurrence of Metabolic Syndrome (MS). The objective of this systematic review and meta-analysis was to determine whether there is an association between the use of PIs and the incidence of MS in HIV-infected patients. Methods: A comprehensive search (including databases such as MEDLINE/PubMed, CENTRAL, LILACS and EMBASE) was performed. Observational studies published until November 2015 were included. Inclusion criteria for primary studies were: study population comprised HIV-infected patients aged 18 years or older and who were receiving HAART; patients assessed according to their use of PIs; DM as defined by the primary study. Heterogeneity was assessed and a pooled analysis was performed using a random-effects model. Results: 3 articles met the inclusion criteria, describing 586 HIV patients. Use of PIs was associated with the development of MS (RR: 2.11; 95% CI 1.28 to 3.48; 〖Chi〗^2:0.04, I^2: 0%; p-value 0.003). Conclusion: Use of PIs in HIV-infected patients is associated with an increased risk of MS. These findings are of relevance for future public policy because it will increase the interest in screening and prevention of MS in an expanding population.